Turbo-discharging turbocharged internal combustion engines - Ramkumar Vijayakumar (2016)
Turbo-discharging (TDC) is a relatively new air system technology that has the potential to better utilise the energy recoverable by a turbine or multiple turbines to depressurize (discharge) the exhaust of internal combustion engines. The energy recovery from the blowdown pulse in isolation from the displacement pulse allows the piston exposed to lower pressures reducing the pumping work leading to higher engine torque and improved fuel economy. This technology has previously been studied in the automotive segment for naturally aspirated and turbocharged (TC) engines with focus on fuel economy and torque improvements. The effect of the exhaust depressurisation on the transient response of a variable geometry turbine (VGT) TC is studied for the first in this research with particular focus on the interaction between two air systems. [Continues.]